Moving the school forward: problems reported by novice and experienced principals during a succession process in Chile - Montecinos, Carmen; Bush, Tony; Aravena, Felipe (Elsevier, 2018)
This article identifies the main problems experienced by two groups of Chilean school principals in a succession process. Problems reported by novice public school principals (n=94) were compared to those reported by their more experienced peers (n=120). Data were gathered through an online survey and eight in-depth interviews. Findings showed that groups did not differ in their overall pattern of responses when problems were categorised at the system level (45%), interactions with people (33%), at the school and territory levels (15%), and within themselves (7%). Differences were observed when comparing the extent to which each group reported problems managing up (interactions with the municipal department of education and Ministry of Education) and managing down (initiating changes in the school's culture and structures). For novice principals, managing up was more challenging and for experienced principals managing down was more pressing. The high frequency and types of problems reported at the system level indicate the need to align policy reforms addressing leadership practices at intermediate and school levels. The findings also suggest guidelines for the professional development programs that extend beyond normative practices for effective school leadership, by also responding to country specific social and organisational structures.